Analisis Yuridis-Normatif Penerapan Legislative Follow-Up terhadap Putusan Mahkamah Konstitusi Terkait Threshold Pemilihan Kepala Daerah - Deva Mahendra Caesar Bimantya; Isharyanto Isharyanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Constitutional Court (MK) “Decision Number 60/PUU-XXII/2024 marks an important shift in the practice of judicial review, whereby the Constitutional Court not only invalidates legal norms, but also establishes new substantive norms in cases involving open legal policy. This action reflects the tendency of positive legislature, which theoretically expands the scope of judicial authority beyond the limits of negative legislature. This study aims to analyse the implications of this ruling on the legislative function of Indonesia Parliament (DPR), particularly in the context of its constitutional responsibility to respond to and accommodate new norms established through court rulings. Using normative legal research methods and a conceptual approach, this study finds that the DPR's suboptimal institutional response to the substance of the ruling indicates serious challenges in harmonising the constitutional system that guarantees the effectiveness of norms, legal certainty, and the principle of checks and balances. This study contributes to proposing a model of inter-institutional coordination or parameters for the judicialisation of norms to ensure the balance of power, as well as criticising and clarifying the boundaries of the roles of each state institution in the context of corrective legislation based on judicial decisions.